A Model of Distance Learning Evaluation in Implementing the Independent Learning Curriculum in Special Circumstances Such as The Covid-19 Pandemic in Indonesia - Meok, Nixson Jeheskial; Kamdi, Waras; Sutadji, Eddy; Widiyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
This research aims to find a model for evaluating the distance learning (DL) process when special circumstances such as a pandemic or disaster occur by comparing the strengths and weaknesses of all the models studied. When the COVID-19 virus outbreak occurred globally, it became a comprehensive trigger for implementing distance education, especially in Indonesia. A new concept known as the Independent Learning Curriculum (ILC) in the distance learning (DL) process has been applied. However, as a result, all regions have not the same readiness to implement this system. Geographical and demographic conditions, which are different, have resulted in the implementation of the DL still encountering various problems. The complaints of education stakeholders regarding student participation are still lacking, and technical and non-technical problems around DL require proper evaluation. The literature study method was carried out to examine the appropriate evaluation model for the DL system with the ICL concept. As a result, an appropriate evaluation selection in the DL process is used the objective-based approach of Tyler's model. In addition, during the corona outbreak, a framework is proposed to achieve the goals according to the evaluation model selected in the DL process.